Implikasi Hukum Pidana dan Hak Asasi Manusia terhadap Praktik Euthanasia di Indonesia - Joice Soraya; Deni Setya Bagus Yuherawan; Galih Setya Refangga (Fakultas Hukum Universitas Islam Indonesia, 2024)
The general principle of the Criminal Code (KUHP) regarding issues of the human soul is to protect human rights to life and dignity. So, under Indonesian law, euthanasia is a legal crime. One major issue raised in the article is how the practice of euthanasia is viewed from a human rights perspective, as well as the implications of criminal law and human rights for euthanasia in Indonesia. The goal of this writing is to identify and analyse the practice of euthanasia from a human rights standpoint, as well as to explain and analyse the implications of criminal law and human rights on euthanasia in Indonesia. This study takes a normative juridical approach, specifically doctrinaire legal research that refers to legal norms. As a result, this study relies heavily on secondary sources with a legal and theoretical background. This research takes both a statutory and a conceptual approach. The research results show that, from a human rights perspective, the practice of euthanasia is in direct conflict with several articles of the 1945 Constitution that regulate human rights, namely Article 28A, Article 28G paragraph (2), and Article 28I paragraph (1), as well as Law Number 39 of 1999 concerning Human Rights, Article 4, Article 9 paragraph (1), and Article 33 paragraph (2). Euthanasia is a crime against people's lives that is regulated under criminal law.